Regional differences in the European labour market - Adalgiso Amendola; Floro Ernesto Caroleo; Gianluigi Coppola (European Regional Science Association (ERSA), 2003)
The European economy is characterised by marked regional differences. In this paper we shall propose some direct methods, using variables of the labour market, of economic branches value added to measure such differences and their evolution in time. In the first section we shall analyse regional disparities in unemployment, employment and the participation rate, while in the second section we shall implement a method of dynamic multivariate analysis -STATIS- in order to study the evolution of the regional structure of the European economy and labour market in the first-half 90's by using a set of regional (NUTS 1) economic indicators.
Keywords: 330